A Critical Study of Cost Approaches in the Accounting Thought: Conceptual Study - Adeeb Abdulwahab Al-Hebry; Ebrahim Mohammed Al-Matari (International Review of Management and Marketing, 2017)
This article has aimed to show such theoretical cost approach in accounting thought. The article has divided the cost approach into two groups, the traditional approach that includes the Volume Based Costing, French Cost Accounting approach and Grenzplankosterechuning approach and Contemporary Cost Approaches which include four approaches Activity-Based Costing, Time-Driven Activity-Based Costing, Resources Consumption Accounting and Lean Accounting. As result of the debate that led to the existence of pros and cons of each approach and no one can declare to say preferential approach on the last absolute.